Polymer Brushes: Mussel‐Inspired Polymer Carpets: Direct Photografting of Polymer Brushes on Polydopamine Nanosheets for Controlled Cell Adhesion (Adv. Mater. 7/2016). Issue 7 (11th February 2016) - Hafner, Daniel; Ziegler, Lisa; Ichwan, Muhammad; Zhang, Tao; Schneider, Maximilian; Schiffmann, Michael; Thomas, Claudia; Hinrichs, Karsten; Jordan, Rainer; Amin, Ihsan
Abstract : Two‐dimensional mussel‐inspired polydopamine (PDA) nano‐sheets are prepared and exploited as a functional surface for grafting various polymer brushes by R. Jordan, I. Amin, and co‐workers, as described on page 1489. The PDA nanosheet and its polymer‐brush derivatives show lateral integrity and are robust; therefore, they can be detached from their substrates. Cell‐adhesion tests show that the PDA nanosheet promotes cell attachment and growth, while a PDA‐based poly(3‐sulfopropyl methacrylate) carpet exhibits non‐fouling behavior.